Adaptation and validation of the university-to-work success scale among Chinese university graduates - Jin, Qiuping; Yu, Kun (Frontiers in Psychology, 2023)
Whether university graduates successfully make the transition from the university to work is critical for their career development. However, a comprehensive measurement of university-to-work success (UWS) that applies across different contexts remains lacking. To address this gap, we adapted and validated the first comprehensive UWS measurement, the university-to-work success scale (UWSS), among samples of Chinese university graduates with three studies. We also provided new construct validity evidence for the scale and examined its measurement invariance across gender. The findings of the current study showed that the 24-item UWSS-Chinese version clearly showed four factors (career satisfaction, income and financial independence, confidence in career future, and adaptation to work) that were consistent with the original scale. Moreover, construct validity analysis revealed that UWSS was positively associated with proposed antecedents (i.e., career adaptability) and outcome (i.e., adult identity). It also showed incremental validity over general indicators of career success (i.e., career adaptability) in predicting adult identity establishment. Additionally, the measurement also showed measurement invariance across gender. Overall, these findings implied that the UWSS-Chinese version had good psychometric properties to be used in future studies and practice in China.